Chemical Composition and In Vitro Evaluation of the Mosquito (Anopheles) Repellent Property of Neem (Azadirachta indica) Seed Oil - Olive Aidoo; Noble Kuntworbe; Fredrick William Akuffo Owusu; Deryl Nii Okantey Kuevi (Journal of Tropical Medicine)
As one of the killer diseases in the world, malaria contributes to child mortality and global death annually. As a result, many reactive mechanisms have evolved to control and repel mosquitoes. The use of synthetic mosquito repellents with N,N-Diethyl-meta-toluamide (DEET) is one of the popular interventions despite its dermatological limitations such as skin irritations. Ethnobotanical reviews have identified that the adoption of natural repellents promises high repellence on mosquitoes with minimal side effects compared with synthetic ones. However, this has received little attention in modern pharmaceutical literature. This research is focused on the formulation of a natural mosquito repellent from the oil extracted from Azadirachta indica (A. Juss). The oil cream was formulated in concentrations of 10% v/w, 12.5% v/w, 15% v/w, 17.5% v/w, and 20% v/w using an in vitro evaluation approach. Pharmacopoeia characteristics of the cream such as pH, viscosity, spreadability, and organoleptic properties were carried out to verify acidity, permeation, and flow properties of the formulated cream. The spreadability rate was inversely proportional to the concentration of the cream in terms of oil content falling from 1.24 gm/s to 0.84 gm/s from concentrations 10% v/w to 20% v/w correspondingly. Skin irritation tests, however, indicated traces of irritation at 20% v/w. Repellency properties of the cream revealed a lasting effect on the mosquitoes, although this was dependent on concentration levels. Formulations of 17.5% v/w and 20% v/w neem seed oil cream had an equal repellency effect of 87.5%, whereas the synthetic repellent had a repellency of 75% within a justifiable time frame for all the formulations. This work shows that plant-based mosquito repellents promise a healthier approach in controlling mosquito bites, protecting the skin, and preventing malaria.